INSTAGRAM SEBAGAI MEDIA INFORMASI DAN PROMOSI MINEWS.ID - Ernawati, Erna (Fakultas Ilmu Dakwah dan Komunikasi, 2024)
The aim of this study was to analyze how Minews.id, an online media portal, utilized Instagram as an information and promotion medium. This study used a qualitative approach by using data collection techniques through observation, interview, and literature review. The result showed that Instagram, as a popular social media platform, was not only used by individuals but also by several companies as a tool to share information related to their products or services with persuasive messages and attract the curiosity and interest of the public.